HUBUNGAN ANTARA LINGKUNGAN KERJA DENGAN TURNOVER INTENTION PADA DEPARTEMEN FINANCE PT XYZ - Ika Novi Yanti; Suzanna Josephine Tobing; Emerald G. M. Tobing (Universitas Kristen Indonesia, 2016)
Human resouce is considered as the key element in supporting organizational’s objectives. Hence maintaining the employees to stay loyal with organization and to always willingly give their best is definitely a homework which organization should do at their utmost. How to mitigate the turnover intention by building a working environment to maintain the talented employees and to put the incapable ones into the turnover circle can ultimately smoothen the way into the set objectives. The ultimate purpose of this research is to know working environment in PT XYZ and how working environment relates with employee’s turnover intention. The used methods are descriptive analysis and correlation of rank spearman by SPSS software version 20. The result shows a negative yet weak relation between working environment and turnover intention for Finance employees at PT XYZ (coefficient correlation is –0,071). The relation itself is not significant, because the significant level is 0,074 (way more than 0,05). Keywords: Human Resource, Turnover, Intention, Turnover Intention, Working Environment